Quality assurance and quality control in surgical oncology: review article - Hardt, Julia; Merkow, Ryan P.; Reißfelder, Christoph; Rahbari, Nuh Nabi (Journal of surgical oncology, 2022)
Even though surgery has remained a key component within multi-disciplinary cancer care, the expectations have changed. Instead of serving as a modality to free a patient of a mass at all means and at the risk of high morbidity, modern cancer surgery is expected to provide adequate tumor clearance with lowest invasiveness. This review summarizes the evidence on quality assurance in surgical oncology and gives a comprehensive overview of quality improvement tools.
Gesehen am 06.06.2023